Iron deficiency in infancy is associated with altered neural correlates of recognition memory at 10 years - Congdon, Eliza L. (2012)
OBJECTIVE: To determine the long-term effects of iron deficiency on the neural correlates of recognition memory. STUDY DESIGN: Non-anemic control participants (n=93) and 116 otherwise healthy formerly iron-deficient anemic (FIDA) Chilean children were selected from a larger longitudinal study. Participants were identified at 6, 12, or 18 months as iron-deficient anemic or non-anemic and subsequently received oral iron treatment. This follow-up was conducted when participants were 10 years old. Behavioral measures and event-related potentials from 28 scalp electrodes were measured during an old/new word recognition memory task. RESULTS: The new/old effect of the FN400 amplitude, where new words are associated with greater amplitude than old words, was present within the control group only. The control group also showed faster FN400 latency than the FIDA group and larger mean amplitude for the P300 component. CONCLUSIONS: Although overall behavioral performance is comparable between groups, the results show that group differences in cognitive function have not been resolved ten years after iron treatment. Long-lasting changes in myelination and energy metabolism, perhaps especially in the hippocampus, may account for these long-term effects on an important aspect of human cognitive development.